The role of food science and technology in humanitarian response. (September 2020) - Bounie, Dominique; Arcot, Jayashree; Cole, Martin; Egal, Florence; Juliano, Pablo; Mejia, Carla; Rosa, Donna; Sellahewa, Jay
Abstract: Background: In humanitarian contexts, ensuring access to safe, nutritious, good quality and culturally appropriate food in the right quantity at the right time and place during an emergency or a protracted crisis is an enormous challenge, which is likely to increase given uncertainties such as climate change, global political and economic instability and emerging pandemics like COVID-19. Several international organizations and non-government organizations have well established systems to respond to food security emergencies. However, the role of food science and technology in humanitarian response is not well understood and is seldom considered in humanitarian circles. Scope and approach: The role of food science and technology in humanitarian response and the importance of addressing the requirements of the local consumers within the local food systems are discussed. Key findings and conclusions: Humanitarian food aid policies focus on immediate and short-term assistance to save lives. The implementation of emergency programs and projects tends to induce dependency on aid, rather than strengthening local food systems and ensuring resilience. Transformative change must embrace innovation across the whole food system with an increased emphasis on food science and technology that addresses local food security, generates employment and contributes to the local economy. There needs to be a move beyond rehabilitating and increasing agricultural production to addressing the whole food system with a view to link humanitarian assistance and longer-term support to sustainable livelihoods and resilience. Highlights: Managing food safety, quality and convenience is crucial in humanitarian situations. Humanitarian Food Science and Technology (HFST) poorly covered up to now. Need to raise awareness on HFST capacity to support food security and resilience. Adequate resources for HFST and multi-stakeholder partnerships must be mobilized. New HFST curricula and training should be collaboratively developed and deployed.